Cognitive evaluation of the hierarchical approach for measuring ego-centered social networks - Nadoh Bergoč, Jana (Metodološki zvezki, 2004)
This paper explores how respondents understand and interpret Antonucci's hierarchical approach (Antonucci, 1986) for measuring egocentered social networks. Cognitive in-depth probes were used to assess how respondents (egos)differentiated among people (alters) that are named in hierarchical circles and what criteria they used to select people from their global social network. In Antonucci's approach emotional criteria are used for selecting alters from the respondentćs global network and placing them into three hierarchical circles that are graphically presented to the respondent. The respondent (ego) is at the center of the three circles. The more central the circle, the closer and more important are the people (alters) within it. The technique begins by asking the individual to look at the diagram of three concentric circles, with a smaller circle in the center containing the word 'You'. Respondents are told that the three circles should be thought of as including people who are important in your life right now but who are not necessarily equally close. Individuals in the inner circle are described as those people to whom you feel so close that it is hard to imagine life without them. The middle circle is described as people to whom you may not feel quite that close but who are still important to you. And finally, outer-circle members are people whom you haven't already mentioned but who are close enough and important enough in your life that they should be placed in your personal network. (Antonucci, 1986). This procedure is often used in research on ego-centered support networks. Only one "name generator" is used for data collection, a technique which is more convenient for respondents and cheaper for the researcher.
Keywords: Measurement; Merjenje; Network analysis; Analiza omrežij; družboslovno raziskovanje; družbena omrežja